Regionalism in Europe Geometries and Strategies After 2000 - von Hagen, Jürgen; Widgren, Mika (Springer US, 2001)
Over the past 40 years, the European Union has been a great force of attraction for new members. At the same time it has entered a host of bilateral and multilateral regional agreements with non-member countries. The result of these developments is a rather unique form of regionalism in Europe, consisting of deep integration within the European Union and a network of sometimes overlapping arrangements involving the Union. Regionalism in Europe: Geometries and Strategies After 2000 brings together a collection of studies of the nature and the implications of this unique regionalism in Europe written by a group of renowned economists from various countries. The issues discussed in this book range from theoretical and institutional aspects to empirical studies of the EU's regional policy, the regional implications of European Monetary Union, and empirical studies of the trade and welfare effects of regional arrangements between the EU and other countries
Keywords: Europäische Union; Regional/Spatial Science; Macroeconomics/Monetary Economics//Financial Economics; Regional economics; Spatial economics; Macroeconomics; Wirtschaftspolitik; Mitgliedsstaaten; Konferenzschrift -- 1998 -- Bonn